Marriage, parenthood and social network: subjective well-being and mental health in old age [dataset] - Becker, Christoph; Kirchmaier, Isadora; Trautmann, Stefan T. (Universität, 2019)
Parenthood, marital status and social networks have been shown to relate to the well-being and mental health of older people. Using a large sample ...